Quantitative and qualitative evaluation of spirometry for COPD screening in general practice - Soumagne, T.; Guillien, A.; Roux, P.; Laplante, J.-J.; Botebol, M.; Laurent, L.; Roche, N.; Dalphin, J.-C.; Degano, B. (Respiratory medicine and research, 2020)
•Approximately 70% of COPD worldwide may be under-diagnosed. Conversely, between 30–60% of patients with a previous physician diagnosis of COPD do not actually have the disease and hence have been over-diagnosed.•Spirometry testing in primary care reliably identifies persistent airflow limitation.•Collaboration with primary care providers may improve appropriate diagnosis of COPD. Proper diagnosis of COPD remains a challenge. Spirometry testing in primary care may help to reduce misdiagnosis, but its reliability as a diagnostic instrument needs to be assessed. To investigate (1) the validity of spirometry testing performed in primary care and (2) the accuracy of the diagnostic of airflow limitation obtained by these tests. Subjects attending a COPD screening programme had screening spirometry performed either by general practitioners (GPs) or by trained nurses or technicians, who had all received two 3-hour training sessions. Subjects with airflow limitation and a subset of subjects with normal spirometry at screening were invited to undergo confirmatory spirometry performed by trained nurses in a pulmonary function laboratory. Of the 4610 subjects who attended the screening sessions, 96.5% had a valid screening spirometry test. A total of 392 subjects attended the confirmatory sessions. Values measured by screening spirometry were satisfactory compared with those of confirmatory spirometry (rc=0.83). Taking confirmatory spirometry as reference, the positive predictive value of screening spirometry for the diagnosis of persistent airflow limitation was 93% with a specificity of 95%. Agreement for the diagnosis of persistent airflow limitation was substantial (k=0.80). Spirometry performed in primary care by trained personnel reliably identifies persistent airflow limitation. This may encourage pulmonologists to collaborate with primary care providers with the aim of improving appropriate diagnosis of COPD.